Chemical Analysis of Morphological Changes in Lysophosphatidic Acid-Treated Ovarian Cancer Cells. Issue 1 (December 2017) - Bailey, Karen; Klymenko, Yuliya; Feist, Peter; Hummon, Amanda; Stack, M.; Schultz, Zachary
Abstract Ovarian cancer (OvCa) cells are reported to undergo biochemical changes at the cell surface in response to treatment with lysophosphatidic acid (LPA). Here we use scanning electron microscopy (SEM) and multiplex coherent anti-Stokes Raman scattering (CARS) imaging via supercontinuum excitation to probe morphological changes that result from LPA treatment. SEM images show distinct shedding of microvilli-like features upon treatment with LPA. Analysis of multiplex CARS images can distinguish between molecular components, such as lipids and proteins. Our results indicate that OvCa429 and SKOV3ip epithelial ovarian cancer cells undergo similar morphological and chemical responses to treatment with LPA. The microvilli-like structures on the surface of multicellular aggregates (MCAs) are removed by treatment with LPA. The CARS analysis shows a distinct decrease in protein and increase in lipid composition on the surface of LPA-treated cells. Importantly, the CARS signals from cellular sheddings from MCAs with LPA treatment are consistent with cleavage of proteins originally present. Mass spectrometry on the cellular sheddings show that a large number of proteins, both membrane and intracellular, are present. An increased number of peptides are detected for the mesenchymal cell line relative to the epithelial cell indicating a differential response to LPA treatment with cancer progression.